Cycloaddition Reactions of Propyne Iminium Salts and Enol Ethers - Kratzer, Philipp; Gerster, Holger; Maas, Gerhard (Synthesis, 2015)
Acetylenic iminium salts (propyne iminium salts) react with cyclic enol ethers in a thermal [2+2] cycloaddition reaction to afford condensed cyclobutene iminium salts. With acyclic enol ethers, a cycloaddition/electrocyclic ring-opening sequence occurs to give (1-alkoxybuta-1,3-dien-2-yl)methane iminium salts as mixtures of diastereoisomers. An analogous scenario is observed with 5-phenyl-2-vinylfuran as the nucleophilic olefinic component. With 1-methoxy-3-trimethylsilyloxy-1,3-butadiene, propyne iminium salts undergo a [4+2] cycloaddition. For all reactions, traces of acid must be quenched with solid K2CO3 or CaO to avoid immediate polymerization of the enol ether.
Keywords: [2+2] cycloaddition; cyclobutene; Diels–Alder reaction; enol ether; iminium salt; microwave activation